2018
DOI: 10.3329/bjsir.v53i3.38262
|View full text |Cite
|
Sign up to set email alerts
|

Environment friendly management of mosquito: a short review

Abstract: Despite the large scale use of insecticides, capacity building, municipality, community and metropolis awareness, and preventive measures to counter vector borne diseases which are mounting day-by-day, new tools are now been introducing to prevent the spread of mosquito transmitted diseases. The low efficacy status of chemical pesticides have lead to the interest of researchers in search of fresh and even more practicable vector control methodologies to be applied. In this regards, multiple alternatives have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Additionally, the Azolla pinnata extracts did not possess any toxic effects on the fish. Many studies on guppy fish, Poecilia reticulata , have shown the abilities of this fish as the biological control of Aedes larvae by its larval-eating potential [ 65 , 66 ]. According a study by Pereira and Olivaira, [ 67 ], Poecilia reticulata has significant potential effects to predate on Aedes aegypti larvae, and this eliminates the breeding ground of larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the Azolla pinnata extracts did not possess any toxic effects on the fish. Many studies on guppy fish, Poecilia reticulata , have shown the abilities of this fish as the biological control of Aedes larvae by its larval-eating potential [ 65 , 66 ]. According a study by Pereira and Olivaira, [ 67 ], Poecilia reticulata has significant potential effects to predate on Aedes aegypti larvae, and this eliminates the breeding ground of larvae.…”
Section: Discussionmentioning
confidence: 99%
“…The red‐eared slider turtle, Trachemys scripta elegans (Emydidae), generally thought to be the most voracious mosquito‐feeding turtle, prefers larger larvae (third and fourth instars) and pupae, and can consume from 500 to 1000 mosquito larvae per hour with sufficient availability 127 . With some supplementary feeding, turtles have been used as biological control agents of mosquitoes in inaccessible aquatic habitats such as retention ponds and seasonal storm water catch basins 128 . Keeping one turtle per water‐storage tank during field trials for a dengue‐control project in Honduras eliminated all mosquito production from this source, and in Louisiana keeping turtles in residential roadside ditches polluted by septic‐tank effluent reduced Cx.…”
Section: Resultsmentioning
confidence: 99%
“…127 With some supplementary feeding, turtles have been used as biological control agents of mosquitoes in inaccessible aquatic habitats such as retention ponds and seasonal storm water catch basins. 128 Keeping one turtle per water-storage tank during field trials for a dengue-control project in Honduras eliminated all mosquito production from this source, and in Louisiana keeping turtles in residential roadside ditches polluted by septic-tank effluent reduced Cx. quinquefasciatus larvae and pupae by more than 99%.…”
Section: 234mentioning
confidence: 99%
“…Despite this, the presence of other prey does not negatively affect the role of predators in controlling the population of mosquito larvae (Stav et al, 2005). Some aquatic bugs (Saha et al, 2007;Valbon et al, 2018Valbon et al, , 2019, larvivorous fishes (Das et al, 2018;Riaz et al, 2018), diving beetles (Choo et al, 2021;Lundkvist et al, 2003), and odonate nymphs (Córdoba-Aguilar et al, 2021;Cozzer et al, 2022;Samanmali et al, 2018) are among the natural predators that can help control the population of mosquito larvae. Odonate nymphs are voracious predators that use unique protractible labium to grab their prey, which includes mosquito larvae, various smaller aquatic invertebrates, and even larvae of fish and amphibians (Zia et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…They have drawn attention to their application in environmentally friendly mosquito control because of their predatory role against mosquito larvae (Subramanian, 2018). To the best of our knowledge, limited research works have been carried out regarding the efficacy of odonate nymphs in mosquito control in the world (Córdoba-Aguilar et al, 2021;Cozzer et al, 2022;Riaz et al, 2018). In Bangladesh, 102 species of odonates including 57 species of dragonflies and 45 species of damselflies have been recorded so far (Shah & Khan, 2020).…”
Section: Introductionmentioning
confidence: 99%